IT as strategic resource in Croatian Companies (Challenges and Acceptance) - Mario Spremić; Ivan Strugar (European Regional Science Association (ERSA), 2001)
Information technology (IT) grows in its importance and becomes one of the strategic means for company development. This paper presents the result of survey on the strategic information system (IS) planning practices of Croatian companies. The results are compared with similar surveys done in Slovenia and Singapore. In large Croatian companies IT is still neglected resource, concerned just as a tool for automation of present business processes. The source of those problems comes from lack of knowledge and interest from top management structures. Thus the significant efforts must be done on the management side. It seems that appears the necessity to develop new hybrid manager profile with additional knowledge in strategic business planning and IT management capabilities.
Keywords: 330